Features using seismic noise study of the deep structure of the west Antarctic - O. I. Lyaschuk; Yu. A. Andruschenko; E. V. Karyagin (Ukrainian Antarctic Journal, 2015)
The article discussed the possibility of application in the area of the Ukrainian Antarctic station «Akademik Vernadsky» passive seismic techniques to study the deep structure of the region. As the probe signal in such methods using seismic noise in a particular region has certain characteristics. Depending on the frequency at which the signal is maximum available to analyze certain depth. Analysis of frequency over time shows that surveillance for different resolution preferably carried out throughout the year. Features macroseismic noise in the region is the presence of signals resulting in the formation of icebergs and shocks of icebergs in the seabed. The method for carrying out further work to study the deep structure of the region passive seismic methods.